تقييم تركيز بعض العناصر الثقيلة من ترب مختارة من مدينة الشطرة - احمد كاظمابتهاج; طالب جوادسناء (University of Thi-Qar Journal of Science, 2019)
The aim of this study to measure the concentrations of five heavy elements in the soil of Shattrah city. We try to detect the extent of contamination levels of heavy metal and make comparison between these level and international standard determinants. We were selected (7) different stations in the city including (old crowded residential, industrial, modern crowded residential, Industrial, area exposers bombed in 2003, and areas closed to the busy streets to vehicles) samples were collected during the month of June and July of 2016 -2015. Using Atomic Absorption Spectrophotometer device (Flam Atomic absorption). Values were arranged ​​[(171.6857, (12.27), (66.4142), (21.5), (20.928) ppm] respectively, the present results indicate that there was high ratio of lead, cadmium and zinc in all study areas and another evidence of soil contamination. هدفت هذه الدراسة الى قياس تراكيز خمسة من العناصر الثقيلة في ترب بعض مناطق مدينة الشطرة ومعرفة مدى تلوثها ومقارنتها بالمحددات القياسية المحلية والعالمية.اذ تم اختيار (7) محطات مختلفة من المدينة (سكنبة مزدحمة قديمة ,صناعية, سكنية مزدحمة حديثة) بالإضافة الى ان البعض منها تعرضت للقصف في عام 2003 م , والبعض الاخر قريب من الشوارع المزدحمة بالمركبات ، تم جمع عينات التربة لغرض قياس العناصر(Pb,Cd,Zn,Cu,Ni) خلال شهر حزيران وتموز للسنة 2016-2015. وقد سجلت معدلات تراكيز العناصر القيم التالية [(171.6857, (12.27), (66.4142), (21.5), (20.928) جزء بالمليون ] على التوالي. باستخدام جهاز امتصاص الطيف الذري الهبي (Atomic absorption (Flam وواضح من النتائج ارتفاع نسبة الرصاص، الكادميوم والزنك في مناطق الدراسة جميعها اما بالنسبة النيكل والنحاس فكانت متفاوتة مقارنة مع الحدود المسموح بها عالمياً وهذا دليل على تلوث التربة